Morphological, Microscopic, and Qualitative Studies of Chemical Composition of [(Michelia Citrata (Noot. & Chalermglin) Q. N. Vu and N. H. Xia)], Family Magnoliaceae Collected in Quan Ba District, Ha Giang Province - Minh Dung, Nguyen; Van Oanh, Ha; Quynh Huong, Le; Thu Lan, Vu Thi; Dang Tuan Manh, Phan; Khanh Ly, Trinh; Tran Mai Phuong, Nguyen; Thuy, Le Thi; Phuong Vien, Nguyen Thi; Manh Tuyen, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 40 No 4, 2024)
Michelia citrata is a species that typically grows in forests and is widely distributed across Thailand and several provinces of Vietnam. Its seeds are also commonly used as a spice. However, there are not many botanical studies currently available on this species. This study was conducted to provide basic data on the morphological and microscopic characteristics and medicinal powder analyses of stems and leaves. At the same time, qualitative analysis was performed to preliminarily identify several groups of substances present in the medicinal leaves. The research results have described in detail the morphological characteristics of the parts, including leaves, stems, flowers, and fruits, and analyzed the micro-anatomy of the stems, leaves, and medicinal powder composition of Michelia citrata . Qualitative results of some groups of substances in medicinal herbs have revealed the presence of flavonoids, alkaloids, sterols, carotenes, fats, saponins, coumarins, cardiac glycosides, reducing sugars, tannins, amino acids, organic acids, and polysaccharides.